Thermodynamic analysis and energy balance for environmental sustainability of simple gas turbine inlet cooling system in AFAM power plant - Aniekan Ikpe; Imoh Ekanem; Enefiok Usungurua (Computational Algorithms and Numerical Dimensions)
The increasing demand for electricity and the growing concerns about environmental sustainability have led to the widespread use of gas turbines for power generation. However, the efficiency of gas turbines is significantly affected by ambient temperature, especially in hot and arid regions. Gas turbine inlet cooling systems are used to lower the inlet air temperature, thereby increasing the power output and efficiency of gas turbines. In this study, a thermodynamic analysis was conducted on a gas turbine currently in use at the Afam power plant in Nigeria. Three turbine air cooling technologies, including spray cooler and wetted media, fogging system technology, and mechanical chiller system, were utilized in order to ensure the sustainability of the system. Additionally, energy and exergy models, together with exergy-economic models, were implemented. The findings showed that the level of sustainability is directly influenced by the reduction in the turbine intake cooling system, as per the design criteria. The refrigeration method, which had an input condition of 15℃, obtained a Sustainability Index (SI) of 2.243. The spray cooling technique had a slightly lower SI of 2.17, followed by the fogging method with a SI of 2.165. The basic turbine system got the lowest SI value of 2.057. The SI declined as the ambient temperatures rose. Both the Enthalpy-Entropy Compensation (EEF) and Waste Exergy Ratio (WER) increased in line with the ambient temperature since they are both dependent on total exergetic destruction. The suggestion is to use the refrigerated cooling method, since it reached lower inlet conditions and had a specific exergy of 2.243, resulting in the least total exergy destruction.